The STAPH Score: A Predictor of Staphylococcus aureus as the Causative Microorganism of Native Vertebral Osteomyelitis - Matsuo, Takahiro (Open Forum Infect Dis, 2020)
BACKGROUND: Staphylococcus aureus (SA) is the most common causative microorganism in native vertebral osteomyelitis (NVO). Few studies have compared the clinical features of NVO due to SA (SA-NVO) and NVO due to other organisms (NSA-NVO). This study was conducted to validate a predictive score for SA-NVO to facilitate NVO treatment without broad-spectrum antimicrobial agents. METHODS: This retrospective study compared the clinical features of patients with SA-NVO and NSA-NVO who were diagnosed from 2004 to 2019. Univariate associations were assessed using χ (2), Fisher’s exact, or Mann-Whitney U test. Multivariable analysis was conducted using logistic regression. The optimal age cutoff point was determined by classification and regression tree analysis. RESULTS: Among 155 NVO patients, 98 (63.2%) had a microbiologically confirmed diagnosis: 40 (25.8%) with SA-NVO and 58 (37.4%) with NSA-NVO. Six predictors, either independently associated with SA-NVO or clinically relevant, were used to develop the STAPH prediction score: atopic dermatitis (Skin) (3 points); recent Trauma (2 points); Age < 67 years (1 point); Abscess (1 point); central venous Port catheter (2 points); and History of puncture (2 points). In a receiver operating characteristic analysis, the area under the curve was 0.84 (95% confidence interval, 0.76–0.91). The best cutoff point was 3. A score ≥3 had a sensitivity, specificity, positive predictive value, and negative predictive value of 58%, 84%, 84%, and 73%, respectively. CONCLUSIONS: The STAPH score has relatively high specificity for use by clinicians to predict SA as the causative microorganism in patients with NVO until results of a confirmatory culture are available.